Alternating Current Electrolysis for the Electrocatalytic Synthesis of Mixed Disulfide via Sulfur–Sulfur Bond Metathesis towards Dynamic Disulfide Libraries. Issue 14 (18th February 2020) - Sattler, Lars Erik; Otten, Chris Josef; Hilt, Gerhard
Abstract: A novel approach of electrolysis using alternating current was applied in the sulfur–sulfur bond metathesis of symmetrical disulfides towards unsymmetrical disulfides. As initially expected, a statistical distribution in disulfides was obtained. Furthermore, the influence of electrode polarisation by alternating current was investigated on a two‐disulfide matrix. The highly dynamic nature of this chemistry resulted in the creation of dynamic disulfide libraries by expansion of the matrices, consisting of up to six symmetrical disulfides. In addition, mixing of matrices and stepwise expanding of a matrix by using alternating current electrolysis were realised. Abstract : Electrical and symmetrical : A novel approach of electrolysis using alternating current was applied in the sulfur–sulfur bond metathesis of symmetrical disulfides towards unsymmetrical disulfides. The highly dynamic nature of this chemistry resulted in the creation of dynamic disulfide libraries by expansion of the matrices, consisting of up to six symmetrical disulfides.